The Role of Influencers in Enhancing Public Understanding of Sharia Insurance in Indonesia - Nonita Fitriani Harahap; Yusrizal Yusrizal; Aqwa Naser Daulay (Journal of Social Commerce, 2025)
This study investigates how public understanding of Sharia Insurance takes form within the lived rhythms of social media, where influence no longer travels through official channels but through the voices of individuals who hold attention, trust, and cultural fluency. In Indonesia, where formal Islamic finance education often falls short of reaching everyday audiences, TikTok influencers have emerged as unexpected educators. This research follows two such figures and explores how their content reshapes not only what their followers know but how they come to know it. Drawing from a qualitative phenomenological approach, the study examines shifts in comprehension among followers exposed to their content. The data reveal a significant increase in understanding, yet the clarity that followed did not translate into action. None of the informants took steps to inquire further or adopt the insurance products they now understood. What emerged instead was a gap between recognition and response, between the ability to grasp meaning and the capacity to move forward. The findings suggest that while influencers play a powerful role in building comprehension, their impact remains suspended when institutional pathways are unclear or absent.